Identity and Its Maintenance in Later Life: A Social Network Approach - MacRae, Hazel (My University, 1987)
This study examines what growing old names for the older women's sense of self-identity. Some gerontological argue that old age constitutes a period of role loss with detrimental impact on identity. A sizable body of data do not support this assumption. The underlying assumption of this study is that identity emerges and is sustained through social interaction. Thus the research focuses on (1) the meaning of 'being old' as defined by older women and (2) the extent to which a positive identity can be retained through social network involvement with family, friends and community leisure activities. Instead of focusing on what is lost, the emphasis was on determining what role relationships are retained and established in old age, and the extent to which these serve to maintain a positive self-image. The research is based on interviews with 142 women over age 65 living in the town of Bridgewater, Nova Scotia. The principle component of this sample comprised 101 women living in their own home or apartments (i.e. community dwelling). Most of the analysis is based on this sample. However, where comparative analysis is useful, these data are supplemented with information from interviews with 31 residents of senior citizens apartment complexes and 10 residents of nursing homes. The findings indicate that the elderly women studied here generally do not view themselves as 'elderly' or 'old'. Age identity is found to be largely situational and more relevant to some interactions than others. The majority have managed to retain a positive identity which is deeply embedded within their informal role involvements and social network ties. As a result, the loss of more formal role relationships had only limited impact on identity. The findings also indicate that a relatively stable small community appears to offer advantages for identity management in old age.
Keywords: Social Network; Identity